The lived experience of menopause for nurses in their workplace : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Psychology (Endorsement in Health Psychology) at Massey University, New Zealand - Smith, Suzanne (Massey University, 2024)
Purpose: To investigate the lived experience of menopause for nurses in their workplace. Background: Most women aged between 45-55 will experience some level of menopause symptoms and by the year 2025 over 1 billion women worldwide would have experienced perimenopause (Grose, 2021). How women experience menopause at work, and what can be done to support them, is particularly important for the nursing profession given its workforce demographic of older cis-women. While there is some research on the experience of menopause and how to improve it in workplaces, it is limited. This is especially so in Aotearoa New Zealand, where there is a paucity of research investigating the effects of menopause on women's health in general, and specifically, in the healthcare workforce. Method: 35 nurses working at Te Whatu Ora Southern who had or were experiencing menopausal/ pre-menopausal symptoms were recruited, using purposive sampling, to complete an anonymous qualitative survey designed for this study. The data were analysed using reflexive thematic analysis informed by a phenomenological framework. Findings: The analysis of the survey data produced five superordinate themes. The first of these themes “The multiplicity experience that is menopause” highlighted the multitude of symptoms that occur with menopause, and which require management within the wider context of the participants’ lives that often include gendered and life-course stresses. The second theme “Challenge to my identity” drew attention to how the menopause experience challenged the participants’ sense of self in terms of who they thought they should be and their perceived identity within their workplace. The third theme “Coat of armour” evidenced a strategy for ignoring or overriding the problem by withholding their concerns and issues and staying silent. The fourth theme “Desires for an Effective Workplace” identified the positive and negative aspects of experiencing menopause in the workplace, and what actions were more or less effective in supporting nurses with menopause at work. Finally, the fifth superordinate theme “Reaching a new stage” celebrated the identification of what can work for these women and how they can reframe this experience into a positive, particularly through knowledge and appropriate support. Conclusions: The stigma associated with menopause shaped these nurses experiences of their workplace, along with a lack of education, sense of support available at work, and appropriate access to services when required. Findings also show the importance of recognising the life course that these women are situated, since multiple physiological, psychological and social factors interacted to affect their experiences and outcomes. The study highlighted a vulnerability related to gender roles and norms; need for improved workplace support; an individual approach to improve retention of nurses; and further research. Understanding the current inequities and the complexity associated with menopause is key to reducing the stigma and offering choice.
Keywords: 520304 Health psychology